Experimental study and numerical simulation of clapboard lead damper. (May 2017) - Cheng, SL; Du, SY; Yan, XS; Guo, Q; Xin, YJ
Two types of clapboard-type lead dampers were designed based on plastic energy absorption of lead metal. The hysteretic curves and energy dissipation properties were studied through low cyclic loading test. Also, the typical restoring load model was extracted. The finite-element numerical model of type-A damper was build according to the characteristics and principle of clapboard-type lead dampers. And the damping effect of high-structural Benchmark model installed with type-A damper was analyzed. The results show that the structure of clapboard-type lead dampers is simple, hysteretic curves are plump, hysteretic properties are steady and yield displacement is small, and thus its energy dissipation ability is excellent. The models of finite element and restoring load of dampers are in good agreement with the results of tests, so they have good applicability. The seismic system installed with type-A dampers has an excellent vibration reduction effect. The top-floor acceleration and displacement control effects are 26.7% and 37.4%, respectively.